2001
DOI: 10.1002/ijc.1191
|View full text |Cite
|
Sign up to set email alerts
|

Plasma prolactin and prostate cancer risk: A prospective study

Abstract: Prolactin, a pituitary peptide hormone with multiple effects, stimulates prostate growth in experimental models. In humans, prolactin receptors are present in the prostate and are particularly abundant in pre-cancerous lesions. This suggests that prolactin could also be involved in the development of prostate cancer. In this study, we tested the hypothesis that elevated levels of circulating prolactin are associated with an increase in prostate cancer risk. We conducted a case-control study nested within the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…97 A similar result was obtained in the Northern Sweden Health and Disease Study (NSHDS), another large prospective cohort. 98 In this second cohort study, the increase in risk was particularly strong in men who provided their blood sample at age 40 ± 50, and who developed a prostate tumour below age 60 (relative risks and 95% con®dence intervals of 1.00, 2.97 (0.84 ± 10.49), and 4.30 (1.19 ± 15.50), for tertiles of IGF-1). Furthermore, prostate cancer risk was positively related to total circulating IGF-1 in two case-control studies (210 and 52 cases, respectively), 99,100 but not in a third, small prospective study that included only 45 incident cases of prostate cancer.…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 79%
See 1 more Smart Citation
“…97 A similar result was obtained in the Northern Sweden Health and Disease Study (NSHDS), another large prospective cohort. 98 In this second cohort study, the increase in risk was particularly strong in men who provided their blood sample at age 40 ± 50, and who developed a prostate tumour below age 60 (relative risks and 95% con®dence intervals of 1.00, 2.97 (0.84 ± 10.49), and 4.30 (1.19 ± 15.50), for tertiles of IGF-1). Furthermore, prostate cancer risk was positively related to total circulating IGF-1 in two case-control studies (210 and 52 cases, respectively), 99,100 but not in a third, small prospective study that included only 45 incident cases of prostate cancer.…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 79%
“…Furthermore, in the prospective NSHDS there was no signi®cant association of prostate cancer risk with direct measurements of fasting plasma insulin, IGFBP-1 or IGFBP-2. 98 Regarding adult body height, many studies do show a positive association, although very modest, with prostate cancer risk (Table 3). A meta-analysis of the prospective studies showed a signi®cant increase in prostatic cancer risk of about 20 ± 25%, comparing upper and lower quartiles of height, and a similar increase was shown for the case ± control studies (results not shown).…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 99%
“…A high blood concentration of PRL in some prostate cancer patients has been reported (Harper et al 1976, Horti et al 1998. Although Stattin et al (2001) have established only a slight correlation between hyperprolactinemia and increased risk of prostate cancer in men, Ben-Jonathan et al (2002) recently reported that PRL increases prostate weight and promotes development of dysplasia and adenocarcinoma of the dorsolateral lobe of the rat prostate. The latter group suggested that PRL might contribute to early carcinogenesis by activating several target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study published to date involved the Northern Sweden Health and Disease Cohort study, which involved follow-up of nearly 30 000 men, including 144 subjects diagnosed with prostate cancer (Stattin et al 2001). This study concluded that there was no correlation between PRL levels and cancer risk.…”
Section: Recent Advances In the Field Of Prl Researchmentioning
confidence: 99%